A comparative analysis of government housing policy and Cape Town City Council housing policy, 1890-1935 - Elias, C. M.(Christiane Marie) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1980.